2017
DOI: 10.1002/aoc.3794
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal preparation and characterization of ZnFe2O4 magnetic nanoparticles as an efficient heterogeneous catalyst for the synthesis of multi‐substituted imidazoles and study of their anti‐inflammatory activity

Abstract: Nanoparticles are key focus of research for a wide range of novel applications. As such, ZnFe 2 O 4 magnetic nanoparticles were synthesized hydrothermally and characterized via scanning and transmission electron microscopies, powder X-ray diffraction, energy-dispersive X-ray and infrared spectroscopies, thermogravimetric analysis and magnetic measurements. They were used as a robust catalyst for the synthesis of a series of biologically active multi-substituted imidazoles using a multicomponent reaction by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…The data also affirm that the synthesized materials are CuO, Co 3 O 4 and NiO, that all the diffraction peaks agreed with the reported standard data; no characteristic peaks were manifested other than metal oxides. The mean granule size (D) of the particles was predestined from the XRD line broadening measurement plying the Scherrer Equation : normalD=true0.89normalλβcosθ0.25em where λ is the wavelength (1.5406 Å), β is the full breadth at the half‐ maximum of the CuO, Co 3 O 4 and NiO line and θ is the diffraction angle. Average crystallite size in the domain of 16‐46 nm were predestined for the CuO, Co 3 O 4 and NiO nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data also affirm that the synthesized materials are CuO, Co 3 O 4 and NiO, that all the diffraction peaks agreed with the reported standard data; no characteristic peaks were manifested other than metal oxides. The mean granule size (D) of the particles was predestined from the XRD line broadening measurement plying the Scherrer Equation : normalD=true0.89normalλβcosθ0.25em where λ is the wavelength (1.5406 Å), β is the full breadth at the half‐ maximum of the CuO, Co 3 O 4 and NiO line and θ is the diffraction angle. Average crystallite size in the domain of 16‐46 nm were predestined for the CuO, Co 3 O 4 and NiO nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…The data also affirm that the synthesized materials are CuO, Co 3 O 4 and NiO, that all the diffraction peaks agreed with the reported standard data; no characteristic peaks were manifested other than metal oxides. The mean granule size (D) of the particles was predestined from the XRD line broadening measurement plying the Scherrer Equation [43][44][45][46][47][48]:…”
Section: Tem and Xrd Of The Prepared Complexes And Metal Oxidesmentioning
confidence: 99%
“…Nano‐zinc ferrite (ZnFe 2 O 4 ) was be synthesized by mixing the stoichiometric solutions of iron(III) nitrate (Fe(NO 3 ) 3 ⋅9H 2 O) and zinc nitrate (Zn(NO 3 ) 2 ⋅6H 2 O) using PEG‐400 as surfactant to prevent aggregation and agglomeration of the nanoparticles in basic medium (pH∼ 12) …”
Section: Nano‐metal Ferrite Catalyzed Heterocycles Synthesismentioning
confidence: 99%
“…On the other hand, other studies have indicated that bulk ZnFe 2 O 4 possesses a normal spinel structure composing of Zn 2+ ions with no magnetic moment in the tetrahedral site to lead to anti‐ferromagnetic behaviors. Nevertheless, the researchers mentioned the possible effect of the crystallite size and synthesis method on the nano‐crystalline zinc ferrite features …”
Section: Introductionmentioning
confidence: 99%